2008
DOI: 10.1590/s1806-83242008000500005
|View full text |Cite
|
Sign up to set email alerts
|

Reviewed evidence about the safety of the daily use of alcohol-based mouthrinses

Abstract: Current scientific knowledge provides clear evidence that alcohol-based mouthwashes can be beneficial in a daily oral health routine, including dental hygiene and plaque control. Several issues are worth discussing, in spite of the wealth of supporting evidence. Despite some undesirable effects to some people, like burning sensation, and some contraindications, like the use by infants, alcohol addicts and patients with mucosal injuries, there is no reason to avoid the use of alcohol-containing mouthwashes as l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 38 publications
(54 reference statements)
0
17
1
3
Order By: Relevance
“…91 The ethanol present in mouthrinses does not contain the carcinogens found in alcoholic beverages, and ethanol has never been demonstrated to be carcinogenic either in laboratory animals or in humans. 92,90 Therefore, the literature does not support dentists' concerns observed in the present survey.…”
Section: Mouthrinse Safety Informationcontrasting
confidence: 73%
See 1 more Smart Citation
“…91 The ethanol present in mouthrinses does not contain the carcinogens found in alcoholic beverages, and ethanol has never been demonstrated to be carcinogenic either in laboratory animals or in humans. 92,90 Therefore, the literature does not support dentists' concerns observed in the present survey.…”
Section: Mouthrinse Safety Informationcontrasting
confidence: 73%
“…In relation to alcohol-containing mouthrinses, there is no scientific evidence to support the professionals' concern. Lemos Jr and Villoria 90 reviewed the literature and concluded that alcohol-containing mouthrinses are safe and should be part of a comprehensive oral health care regimen. The same conclusions were demonstrated in a systematic review published by Silverman and Wilder.…”
Section: Mouthrinse Safety Informationmentioning
confidence: 99%
“…Mass-media approaches and oral cancer secondary preven-tion should be targeted to those at most risk of oral cancer. [4][5][6][7][8][9][10][11][12][13][14][15][16][17] These individuals are described as very unlikely to become regular dental attendees.…”
Section: Discussionmentioning
confidence: 99%
“…Although most information relies yet on biological plausibility, some authors call attention to mouthrinse adequate and proper indications. 6 Some authors have reported that the effect of socioeconomic status on oral cancer is given little recognition in a predominantly medical model approach to research and prevention on the risks of the disease. A paper published in 2008 summarizes results from studies which had included this variable as an outcome or an independent predictor.…”
Section: Risk Factors: What Is Different From the Already Known?mentioning
confidence: 99%
“…The alcohol content of mouthrinses, besides having antiseptic properties, serves the purpose of breaking down or dissolving active principles, in addition to that of preserving the formula components, although such content does not directly contribute to effective biofilm and gingivitis control [5]. However, there are some contraindications in the use of alcohol-based mouthrinses, like the use by infants, pregnant women, alcohol addicts, and patients with mucosal injuries.…”
Section: Introductionmentioning
confidence: 99%